Ripper letter from hell - Tylor, Evant; Curtis, John; Eyres, John (USA : Prophecy Entertainment)
By the time she was 16, Molly Keller had already lived to tell a very bloodcurding tale: she was the only survivor of a violent massacre while on an otherwise peaceful island vacation with her friends. Disturbed by her horrific past, Molly focuses all of her energies in researching the psyche of serial killers. This leads her to the forensic science program at Berkeley under famed author and man hunter, Prof. Martin Kane. But before long, the evil that had claimed Molly's friends is seemingly loose again-this time on the campus. A reluctant Molly joins the study group which is fixated on tracking the gruesome murderer. But events take an eerie turn when the students discover that the killer's modus operandi matches London's oldest unsolved murderer: those of Jack-the-Ripper. Molly's friends fall victim around her, one at a time, while the remaining group works feverishly to uncover the identity of the copycat killer. As the past reawakens, Molly is forced to face the terrifying secret behind the stalker's return, and the entire class soon realizes that it's a history they don't want to repeat.
Editor, Amanda L. Kirpau ; music, Peter Allen ; director of photography, Thomas Harting
Keywords: Horror films; Murder in motion pictures